Implementation of Learning Management in Increasing the Learning Achievement of MI Ar-Rahmah Students - Khoirudin, Moch. Alfin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study aims to determine the implementation of learning management in increasing learning achievement at MI Ar-Rahmah. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used was observation and interview techniques. This participatory observation technique was carried out to observe the geographical location in the form of a location plan and environmental conditions, vision, mission, strategy for MI Ar-Rahmah. the implementation of Learning Management at Madrasah Ibtidaiyah Ar-Rahmah goes through planning, organizing, directing and assessing activities. Each of these stages was carried out with good criteria by Madrasah Ibtidaiyah Ar-Rahmah teachers. However, based on the results of data analysis, it was revealed that research findings provided answers to the research problem formulation. In planning activities the teacher is obliged, with superior control, to prepare and develop his creativity so that the results are effective and efficient.